Usos de si e testemunhos de trabalhadores docentes readaptados - Lemes, Núbia Cristina dos Santos (2019)
The objective of this research is to understand how the readjusted teacher's life and work experience is presented, based on his testimonies. The methodology used was qualitative, using semi-structured individual interviews. The interviews were transcribed and organized according to Graham Gibbs thematic coding and categorization. The ergological perspective conceived by Yves Schwartz was the contribution in the interpretation of the testimonies of life and work in the uses of the body-self. The activity clinic based on Yves Clot made it possible to understand the situations of amputation of the power to act. The knowledge of life from Georges Canguilhem allowed us to associate health with the normative capacity of the human living. Philippe Davezies made it possible to understand the relationship between the involvement of affective dimensions at work and the illness of teachers, and Christophe Dejours provided the relational basis between work organization and psychological distress. One teacher and five teachers participated in the research that included the population of readapted teachers from Iporá, Goiás State.The analysis of the testimonies revealed how teachers' lives and work intersect and how the body-self was affected by the dramatic experiences experienced at work. Upon becoming readapted, teachers assume the role of library facilitator and pedagogical advisor, however, in schools they perform various activities. Out of the classroom, the readjusted teacher seeks new meanings in the tasks assigned to him. Even so, it stands out in the testimonies that the meaning of work, for the readjusted teacher, lies in the classroom activity. It was unanimous in the testimonies the existence of stigma before the professional collective of the readapted teacher. For these, the new objects of work replaced the object / subject / student. These new objects became the quality of emotionally competent objects. The survey also revealed that Gestar-SEDUC does not have enough staff for the state demand that, according to GESPRE data for 2017, out of a total of 10,100 permanent teachers, had 100 teachers temporarily or permanently readapted, and 54% was between 41 and 50 years old. In 2018, the number of readaptations increased to 167 teachers, but the highest readaptation rate remained at the same age, estimated at approximately 50%. The survey confirmed 80% of pathological disorders in females and that there is still no clarification from the competent bodies on how to deal with the teacher readjusted at school. The rate of illness in the category is increasing. In addition to teachers who are legally removed from professional practice, the same amount of sick teachers is off the classroom in an unofficial manner. The survey also found that the Goiás State Workers Union has not required teachers' health care. Because of all this, public policies lack effective actions that can create possibilities for recovery of the readjusted teacher's health and adequate environmental and organizational working conditions.